PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN MOTIVASI BELAJAR TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI (STUDI PADA SISWA SMK NASIONAL PADANG) - Rahmat Ramadhan; Marwan Usman; Armiati Armiati (Jurnal Ecogen, 2018)
This study aims to determine the Effect of Socioeconomic Status of Parents Against Learning Motivation, Influence Motivation Learning Interest Continue Study to Higher Education and Influence of Parents' Socioeconomic Status on Interest Continue Study to Higher Education.                The population in this study is the students of class XII SMK National Padang Academic Year 2017/2018 amounted to 77 students. Intruments in this study used questionnaires. Trial of research instrument with validity test and reliability test conducted on 30 students at SMK Nusatama Padang. Data analysis technique used is path analysis technique using SPSS ver program. 16.0.                The results of this study show: First there is a positive influence and significant socioeconomic status of parents to the motivation of students learning class XII SMK National Padang Year 2017/2018, meaning the higher the level of socioeconomic status of parents then the student learning motivation also increases. Second there is a positive and significant influence on the socio-economic status of parents on the interest to continue studies to college students of class XII SMK Padang National Academic Year 2017/2018, it can be interpreted that the higher socioeconomic status of parents will increase the interest of students of SMK Nasional Padang to continue education to university Thirdly there is a positive and significant influence of learning motivation toward the interest of continuing study to college students of class XII SMK National Padang Year 2017/2018 which shows that the higher the students' learning motivation, the higher the interest of students of SMK Nasional Padang to continuing education to college. Keywords: socioeconomic status of parents, motivation to study and interest in continuing study to public universities